PENGARUH TERPAAN IKLAN JUDI ONLINE DI MEDIA SOSIAL, TINGKAT PENGAWASAN ORANG TUA, DAN INTENSITAS KOMUNIKASI PEER GROUP TERHADAP MINAT BERMAIN JUDI ONLINE - Yusuf Akbar, Muhammad; Pradekso, Tandiyo; Surayya Ulfa, Nurist (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
This study aims to analyze the influence of online gambling advertisement exposure on social media, the level of parental supervision, and the intensity of peer group communication on the interest in online gambling. This research is motivated by the increasing interest in online gambling in Indonesia since the pandemic, accompanied by rising transaction values year after year. Factors such as the prevalence of online gambling ads on social media, lack of parental supervision, and peer influence are considered the main triggers. The research method used is a quantitative approach with a positivistic paradigm. Data were collected through questionnaires distributed to respondents who met the research criteria. The results show that exposure to online gambling advertisements on social media has a significant influence on the interest in online gambling. The level of parental supervision also has an effect, although not as strong as the influence of advertisements. The intensity of peer group communication has a significant impact, indicating that peer influence is an important factor in the interest in online gambling. This research is expected to provide new insights for future studies in the field of communication and help raise public awareness about the dangers of online gambling and the importance of parental supervision and good communication with children.